Calcitriol pulse therapy is not more effective than daily calcitriol therapy in controlling secondary hyperparathyroidism in children with chronic renal failure - Ardissino, Gianluigi; Schmitt, Claus P.; Testa, S.; Claris-Appiani, A.; Mehls, Otto (Pediatric nephrology, 2000)
Calcitriol oral pulse therapy has been suggested as the treatment of choice for secondary hyperparathyroidism, but its efficacy and safety are still under discussion. The present randomized multicenter study compares the effect of an 8-week course of daily versus intermittent (twice weekly) calcitriol therapy on parathyroid hormone (PTH) suppression in 59 children (mean age 8.4±4.7 years) with chronic renal insufficiency (mean Ccr 22.4±11.6 ml/min per 1.73 m2) and secondary hyperparathyroidism. After a 3-week washout period, the patients were randomly assigned to treatment with daily oral calcitriol (10 ng/kg per day) or intermittent oral calcitriol (35 ng/kg given twice a week). The calcitriol dose was not changed throughout the study period of 8 weeks. At start of the study, the median intact PTH (iPTH) level was 485 pg/ml (range 83-2032) in the daily group (n=29) and 315 pg/ml (range 93-1638) in the intermittent group (n=30). After 8 weeks, the respective median iPTH concentrations were 232 pg/ml (range 63-1614) and 218 pg/ml (range 2-1785) (ns). The mean iPTH decrease from baseline was 19.2±57.8% and 13.7±46.7% respectively (not significant). Calcitriol reduced the iPTH concentration in 23/29 patients in the daily group and in 21/30 in the intermittent group. One episode of hypercalcemia (>11.5 mg/dl) was observed in both groups and a single episode of hyperphosphatemia (>7.5 mg/dl) was observed in the daily group. It is concluded that oral calcitriol pulse therapy does not control secondary hyperparathyroidism more effectively than the daily administration of calcitriol in children with chronic renal failure prior to dialysis.
Gesehen am 11.01.2021